An Irish country family [large type] - Taylor, Patrick, 1941- (Taylor, Patrick, 1941- Irish country novel, 2019)
"Before Doctor Barry Laverty joined Doctor Fingal O'Reilly's practice in the colorful Irish village of Ballybucklebo, he was an intern, working long hours, practicing new medical techniques, falling in love, and learning what is most important in the medical field for a family physician -- the bonds of family, friendships, and human kindness. Years later, Barry practices everything he has learned in Ballybucklebo, a lovely village where neighbor looks after neighbor. And while his own efforts to start a family with his wife Sue have been frustrated, the community around him couldn't be stronger as they work together to show their solidarity. Shifting effortlessly between the two time periods, [...] Patrick Taylor continues the story of these beloved characters while vividly bringing the daily joys and struggles of this delightful Irish village to life." --